Risk management analysis in electrochlorination plant using House of Risk - Shanti Kirana Anggraeni; Nuraida Wahyuni; Desi Ramdhani (Journal Industrial Servicess, 2022)
XYZ Corp. is a petrochemical company with several Electrochlorination Plants (ECP) to produce chlorine. ECP is a room with a high risk because there can be a buildup of hydrogen gas in the ECP room, which can cause an explosion. Therefore, it is necessary to carry out risk analysis in activities at ECP to mitigate possible risks or disturbances. The purpose of this study is to identify risks and risk agents as well as risk agents that are prioritized in the Electrochlorination Plant (ECP), using the House of Risk (HOR) method, which consists of 2 phases. The first phase is identifying risk events and agents, which are then measured on the severity and occurrence levels and calculating the Aggregate Risk Priority (ARP) value. This study found that 17 risk events and 11 selected risk agents must be prioritized to be resolved. They contribute to an 80% cumulative value of the highest Aggregate Risk Potential (ARP), which means it has the most significant influence on daily operations. Therefore, the company must overcome this by taking preventive steps to minimize or eliminate the source of the risk.